Increased Incidence of Alzheimer’s Disease: Lifestyle and Supplementation with Nutraceuticals and Probiotics as New Prevention and Treatment Strategies (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Alzheimer’s disease is a neurodegenerative disorder that mainly affects individuals over the age of 60, progressively rendering them unable to care for themselves. The incidence of the disease has increased dramatically in recent decades, posing a significant challenge to healthcare systems worldwide. Currently, there is no definitive and effective treatment, partly because the etiopathogenesis of the disease has not been fully elucidated. The disease, characterized histologically by amyloid plaques and neurofibrillary tangles, has very likely a multifactorial etiology. Neuroinflammation is thought to be the primary cause of the neurotoxicity observed in brain areas, including hippocampus and prefrontal cortex. Innovative methodologies and new tools derived from artificial intelligence have allowed us to define several risk factors and identify nutraceuticals and probiotics capable of counteracting neuroinflammation and disease progression.
Keywords: Alzheimer’s disease; neuroinflammation; oxidative stress; microglia; nutraceuticals; probiotics